1991
DOI: 10.3133/ofr90584
|View full text |Cite
|
Sign up to set email alerts
|

Selected references for the Puget-Willamette Lowland regional aquifer-system analysis, Puget Sound Lowland, Washington

Abstract: As a preliminary step in the comprehensive study of the Puget-Willamette Lowland, a literature search was made and bibliographies compiled for each of the subareas. The purpose of this report is to provide a bibliography of selected references on the hydrology of the Puget Sound Lowland aquifer system. This bibliography emphasizes the groundwater resources and includes studies of the glacial geology, geochronology, geophysics, structural geology and tectonics, surface water, evapotranspiration, and other perti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…References to the many studies of the geology and hydrology of the Puget Sound Lowland can be found in a bibliography compiled by Jones (1991) as part of a regional aquifer system analysis (RASA) carried out by the U.S. Geological Survey. Vaccaro (J.J. Vaccaro, U.S. Geological Survey, written commun., 1993) summarizes many of the results and conclusions from the RASA study, including analyses using cross-sectional numerical models in various hydrogeologic settings in the Puget Sound Lowland.…”
Section: Methods Of Studymentioning
confidence: 99%
“…References to the many studies of the geology and hydrology of the Puget Sound Lowland can be found in a bibliography compiled by Jones (1991) as part of a regional aquifer system analysis (RASA) carried out by the U.S. Geological Survey. Vaccaro (J.J. Vaccaro, U.S. Geological Survey, written commun., 1993) summarizes many of the results and conclusions from the RASA study, including analyses using cross-sectional numerical models in various hydrogeologic settings in the Puget Sound Lowland.…”
Section: Methods Of Studymentioning
confidence: 99%
“…A list of the pertinent studies (Jones, 1991) was compiled as part of this investigation to assimilate the available information; many of the previous investigations are listed in the "Selected References" section of this report. A short summary of selected previous investigations related to geology, surface water, and ground water is given in the following paragraphs.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…Geologic structure (Gower, 1978;Cheney, 1987;Jones, in press) appears to separate the aquifer system into discrete ground-water basins. These basins are drained by rivers that carry water from the adjacent mountains to lowlands and then to Puget Sound, Hood Canal, and other saltwater bodies that are inland arms of the Pacific Ocean.…”
Section: Physical Settingmentioning
confidence: 99%
See 2 more Smart Citations